How Gesture Input Provides a Helping Hand to Language Development - Özçalışkan, Şeyda; Dimitrova, Nevena (Seminars in Speech and Language, 2013)
Children use gesture to refer to objects before they produce labels for these objects and gesture–speech combinations to convey semantic relations between objects before conveying sentences in speech—a trajectory that remains largely intact across children with different developmental profiles. Can the developmental changes that we observe in children be traced back to the gestural input that children receive from their parents? A review of previous work shows that parents provide models for their children for the types of gestures and gesture–speech combinations to produce, and do so by modifying their gestures to meet the communicative needs of their children. More importantly, the gestures that parents produce, in addition to providing models, help children learn labels for referents and semantic relations between these referents and even predict the extent of children's vocabularies several years later. The existing research thus highlights the important role parental gestures play in shaping children's language learning trajectory.
Keywords: Gesture production; gesture input; language development; gesture–speech combination